Disclosing the relationship between public service motivation and job satisfaction in the Chinese public sector: A moderated mediation model - Zhang, Ying (Frontiers in Psychology, 2023)
Despite the relationship between public service motivation and job satisfaction is widely discussed, rare studies explore the theoretical mechanism of this relationship. Through integrating public service motivation, role overload, job satisfaction, and marital status, this study explores psychological mechanisms and boundary conditions of the relationship between public service motivation and job satisfaction. Data was collected from 349 public employees in eastern China. Empirical results reveal that public service motivation is positively related to job satisfaction by decreasing role overload. Moreover, marital status moderates the relationship between role overload and job satisfaction, as well as moderates the indirect effect of public service motivation on job satisfaction through role overload. These findings advance our understanding of the psychological mechanism and conditional effect of PSM in relation to job satisfaction and provide valuable insights into how to improve public employees’ well-being.